2017
DOI: 10.1136/bmjinnov-2016-000188
|View full text |Cite
|
Sign up to set email alerts
|

New technical solution to minimise noise exposure for surgical staff: the ‘silent operating theatre optimisation system’

Abstract: The increasing number of technical equipment in the operating room (OR) is resulting in significantly higher noise levels. The more complex and sophisticated the surgical procedure is, the more essential it is for all team members of the OR to work together in a harmonious fashion to process and manage their demanding team tasks. With increasing noise in OR, the risk of more frequent errors also increases. The reduction of noise production in the OR is possible but limited. The aim of this study was to develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
(13 reference statements)
0
16
0
Order By: Relevance
“…Further studies to investigate the reasons of the different acceptance of the system within the surgical team focusing on communication structure and technical benefits should be planned. Friedrich et al could show that SOTOS © reduces questions and general communication during the surgery [21]. Bypassing the distance between surgeon and the rest of the team in the da Vinci OR could explain a subjective improvement for the surgeon and the team through SOTOS © .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Further studies to investigate the reasons of the different acceptance of the system within the surgical team focusing on communication structure and technical benefits should be planned. Friedrich et al could show that SOTOS © reduces questions and general communication during the surgery [21]. Bypassing the distance between surgeon and the rest of the team in the da Vinci OR could explain a subjective improvement for the surgeon and the team through SOTOS © .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed a negative effect of noise in the OR for the whole surgical team [ 3 5 ]. Friedrich et al developed SOTOS © and were the first to show this new technical device to minimize noise exposure for cardiac surgery teams [ 21 ]. SOTOS © comprises not just noise reduction, but also shields disturbing environmental noise and offers immediate and direct voice information by the individual hearing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations